An Empirical Analysis of the Determinants of Bank’s Default Risk Across Europe - Theocharous, Savvas / S.T (2018)
This thesis examines the joint role of macroeconomic and micro-bank specific determinants of bank risk using Z-score as quantifying measure of bank stability. We focus on the countries of the European region, analysing individual bank level data from 2011 to 2017, a period that the financial crisis effects weaken and hence did not largely influenced our data. Implementing a static panel data analysis, we investigate the effects of the bank risk determinants using five time-varying Z-score formulas. Also, we separate the sample according the bank specialization, examining the same bank’s risk factors and ultimately, we employ NPL as an alternative risk measure and examine two additional explanatory variables. Regarding the micro-bank specific variables, our results show that the bank size, the cost efficiency and the revenue diversification have a significant explanatory power on bank risk. Additionally, almost all the macroeconomic determinants included in our study are identified as significant, contributing largely to the overall bank risk. The empirical analysis shows the consistency of our model through time and in comparison, with the alternative risk measure. Finally, the specialization regressions lead to conclusion that the industry concentration has large and different impact on each banking sector with cooperative and saving banks being more stable in high concentrated markets.